2009
DOI: 10.1038/jhg.2008.14
|View full text |Cite
|
Sign up to set email alerts
|

Case–control association study of 59 candidate genes reveals the DRD2 SNP rs6277 (C957T) as the only susceptibility factor for schizophrenia in the Bulgarian population

Abstract: The development of molecular psychiatry in the last few decades identified a number of candidate genes that could be associated with schizophrenia. A great number of studies often result with controversial and non-conclusive outputs. However, it was determined that each of the implicated candidates would independently have a minor effect on the susceptibility to that disease. Herein we report results from our replication study for association using 255 Bulgarian patients with schizophrenia and schizoaffective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 38 publications
(52 reference statements)
1
70
0
3
Order By: Relevance
“…All studies used a case-control design and clinical diagnoses of psychiatric disorders were made by interviews or examination of patients' records by psychiatrists. Seven articles described screening of the control group for psychiatric disorders (Betcheva et al, 2009;Crisan, 2006;Jonsson et al, 2008;Lee et al, 2006;Ozbek et al, 2008;Sazci et al, 2005;Vilella et al, 2005) and five articles reported matching of the control group (Crisan, 2006;Jonsson et al, 2008;Lee et al, 2006;Sazci et al, 2003Sazci et al, , 2005. All samples used a PCR-based method for genotyping the A1298C polymorphism.…”
Section: Mthfr A1298cmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies used a case-control design and clinical diagnoses of psychiatric disorders were made by interviews or examination of patients' records by psychiatrists. Seven articles described screening of the control group for psychiatric disorders (Betcheva et al, 2009;Crisan, 2006;Jonsson et al, 2008;Lee et al, 2006;Ozbek et al, 2008;Sazci et al, 2005;Vilella et al, 2005) and five articles reported matching of the control group (Crisan, 2006;Jonsson et al, 2008;Lee et al, 2006;Sazci et al, 2003Sazci et al, , 2005. All samples used a PCR-based method for genotyping the A1298C polymorphism.…”
Section: Mthfr A1298cmentioning
confidence: 99%
“…These studies have yielded largely inconclusive and often mixed results (Betcheva et al, 2009;Feng et al, 2009;Gaysina et al, 2008;Gilbody et al, 2007;Pan et al, 2009;Yu et al, 2004;Yuan et al, 2008). MTHFR is a crucial enzyme involved in one-carbon metabolism (OCM), a folate-mediated pathway essential for purine and thymidylate biosynthesis, the methylation of DNA and amino acids, and is necessary for reactions forming neurotransmitters (Sugden, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of association of rs6675281and schizophrenia is in line with the literature. 29,43,44 The rs3738401 SNP, together with rs751229, forms a common DISC1 haplotype, HEP3, spanning 62 kb from intron 1 to exon 2. HEP3 (T-A) was found to be overtransmitted to males with schizophrenia spectrum psychosis and severe mood disorders.…”
Section: Association Of Disc1 Missense Variants With Ursmentioning
confidence: 99%
“…Dysfunction of the one-carbon metabolism has been linked to a range of disorders including neural tube defects [177,178], autism [179], leukemia [180,181], dementia [182][183][184], colorectal cancer [183,185], cardiovascular disease [186] and congenital abnormalities [187,188]. Genetic studies on associations between genetic variants in Mthfr and various major psychiatric disorders such as schizophrenia, bipolar disorder and unipolar depressive disorder, have yielded largely inconclusive and often mixed results [189][190][191][192][193][194][195]. Given the essential role of Mthfr in brain function and neurodevelopment [196,197], and the fact that family and twin studies have established considerable shared genetic variance between psychiatric disorders [198][199][200], a recent meta-analysis (on a total of more than 29,000 subjects) tested whether genetic variation in Mthfr contributes to the shared genetic vulnerability of schizophrenia, bipolar disorder and unipolar depressive disorder [201].…”
Section: Administration Of Thc or Cannabis Elicitsmentioning
confidence: 99%